Trends and Challenges in Mixed Methods Educational Research: A Comprehensive Analysis of Empirical Studies - Zhao, Xiantong; Xu, Renying (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
The mixed methods research approach combines quantitative and qualitative methodologies to comprehensively understand complex research questions, particularly valuable in educational studies. This study critically examines adopting and utilizing mixed methods in Chinese educational research by analyzing 105 empirical studies published in major Chinese academic databases from 2002 to 2023. Using a framework based on established mixed-methods criteria, researchers evaluated these studies across five dimensions: research objectives, rationale for mixed methods, methodology and sample size, design type, and journal category. The findings reveal that while mixed methods usage in Chinese educational research has grown significantly since 2018, especially with a preference for explanatory sequential and concurrent designs, many studies lack clarity in articulating the rationale behind their methodological choices. This lack of transparency limits the potential of mixed methods to address educational challenges in depth. Additionally, data collection methods remain limited, relying on questionnaires and interviews and less frequently using techniques such as observations and experiments. High-quality journals show a preference for rigorously conducted mixed-methods research, underscoring the importance of methodological rigor. This study advocates for improved alignment of research questions, clearer rationale, and diversified data collection to enhance methodological robustness in future mixed methods educational studies in China.